REPEAT ORDER RECOMMENDATION MODEL TO DIGITALIZE THE CANTEEN - Dhiani Tresna Absari; Liliana Liliana; Daniel Soesanto; Susana Limanto (Jurnal Bisnis Terapan, 2023)
The canteen is a campus facility that the academic community needs. However, because it is considered a complementary facility, business processes in the canteen are carried out conventionally, relying on paper-based recording. In addition, at certain hours, especially at lunchtime, the canteen is overloaded due to too many orders co-occurring. This buildup of charges is due to the need for canteen preparation in preparing orders from its buyers. Therefore, this study developed an ordering system to recommend the menus that customers likely purchase. The case study used in this research is the Keluwih canteen on the Tenggilis campus, owned by the University of Surabaya. This research used the waterfall method and focused on three main canteen processes: online ordering with a repeat order recommendation model for sellers, delivery services, and payments using the e-wallet. The study's results were assessed qualitatively, and the respondents felt they got better and faster service. Furthermore, with this system's e-canteen application, the time needed to complete a transaction at the campus canteen can be done efficiently to increase customer satisfaction and employee productivity from tenants.